Consumption of fruits and vegetables and its association with sleep duration among Finnish adult population: a nationwide cross-sectional study - Thapa, Anupa; Lahti, Tuuli; Maukonen, Mirkka; Partonen, Timo (Frontiers in Nutrition, 2024)
Sleep and diet are crucial determinants of overall health and wellbeing, with the potential to mutually influence each other. This study examined the association between sleep duration and fruits and vegetables (FV) consumption among Finnish adults, considering the role of demographic, socio-economic and chronotype as confounders. The study analysed data from the National FinHealth 2017 Study involving 5043 adults aged 18 years and above. Participants reported their habitual sleep duration, and dietary consumption through a validated selfadministered questionnaire. Mean dietary consumption was compared across three sleep duration categories (short, normal, long), revealing that short sleepers consumed 37 g/d fewer FV, and long sleepers consumed 73 g/d fewer FV than normal sleepers. Additionally, significant differences were observed in the consumption of various subgroups of FV among these sleep categories. Binary logistic regression analyses consistently demonstrated significant negative association between FV consumption and both short and long sleep duration across all models, even when adjusted for a range of covariates. Specifically, short sleep was significantly associated with lower consumption of total FVs, green leafy vegetables, root vegetables, and fruit vegetables, with similar patterns observed for long sleepers. Notably, these associations persisted after controlling for demographic and lifestyle factors, including chronotype, which did not significantly affect the relationship between sleep duration and FV intake. A sensitivity analysis, which excluded energy under-reporters, further substantiated these associations, emphasizing the potential influence of underreporting on dietary assessments. Linear regression analyses revealed a positive but non-significant association between sleep duration and Total Fruit and Vegetable Consumption (TFVC) that became significant when excluding energy under-reporters, particularly in model 1. In conclusion, this study suggests a consistent pattern where deviation from normal sleep duration was associated with decreased FV consumption, suggesting the need for considering sleep patterns in dietary intervention. The substantial role of accurate energy reporting in elucidating these associations is highlighted. Further research, including longitudinal studies, is needed to better understand the mechanisms underlying these associations.